1991
DOI: 10.1002/ajmg.1320400207
|View full text |Cite
|
Sign up to set email alerts
|

On the inheritance of primary spontaneous pneumothorax

Abstract: We report on 15 families with familial primary spontaneous pneumothorax detected through a retrospective study of a large group of male patients. Genetic analysis of these families together with 14 families from the literature in which enough details were available suggested 2 possible models of inheritance. First, the familial cases are due to an autosomal dominant gene with incomplete penetrance, the penetrance being lower in females (21%) than in males (50%). Second, the familial cases represent a heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 17 publications
5
50
0
2
Order By: Relevance
“…The lung cysts are reported to be round, to contain blood vessels, and to exist predominantly subpleurally, mediastinally, and in the lung bases and lower lobes (10). The round, thin-walled lung cysts in the present patient were located predominantly in the lower lobes, and these findings were compatible with the previous report.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lung cysts are reported to be round, to contain blood vessels, and to exist predominantly subpleurally, mediastinally, and in the lung bases and lower lobes (10). The round, thin-walled lung cysts in the present patient were located predominantly in the lower lobes, and these findings were compatible with the previous report.…”
Section: Discussionsupporting
confidence: 92%
“…Although the patient with BHD syndrome may repeatedly develop pneumothorax, it is different than that in LAM in that pulmonary function is preserved, and the patient will not progress to respiratory failure (10). The present patient developed pneumothorax, so partial lung resection was performed.…”
Section: Discussionmentioning
confidence: 69%
“…Approximately 11.5% of patients presenting with spontaneous pneumothorax report a positive family history of the condition (1). Familial spontaneous pneumothorax (FSP) was initially reportedBHD syndrome (OMIM 135150) is a rare autosomal dominantly hereditary disease, which was firstly described in 1977 by Birt et al (8).…”
Section: Introductionmentioning
confidence: 99%
“…5 There is not only genetic but also clinical heterogeneity in FPSP. [6][7][8] The clinical picture of the disease may come to light through the combinations of different organ and system involvements. 8 Although Koivisto and Mustonen reported that the autosomal recessive inheritance was responsible for the 2 cases with FPSP, most researchers hold the idea that the autosomal dominant inheritance responsible for FPSP.…”
mentioning
confidence: 99%
“…Even though the male gender is dominantly affected by FPSP, it can still be seen in both genders. 6,7,10,11 The aim of this study was to investigate the demographic, clinical, laboratory, radiological and hereditary characteristics of 8 PSP cases within an extended family in which frequent consanguineous marriages are seen.…”
mentioning
confidence: 99%